A socioenvironmental approach to the nosogenic potential of freshwaters with presence of thermotolerant free-living amoebae in Costa Rica - Alvarado-Ocampo, Johan; Romero Zúñiga, Juan José; Castro, Julián; Chaves Monge, Frida; Ruiz Campos, Marco; Bustamante Cortés, Alexa; Abrahams Sandí, Elizabeth; Retana Moreira, Lissette (Frontiers in Public Health, 2025)
IntroductionWithin the group of free-living amoebae (FLA), the genus Naegleria stands out for including species adapted to high temperatures, such as the facultative human parasite Naegleria fowleri, that can be found in various terrestrial and aquatic environments. Characterizing and monitoring water bodies is crucial for determining the presence of pathogenic microorganisms and assessing the risk of infection. In this study, we propose an environmental survey to identify physicochemical parameters related to the presence of Naegleria in natural freshwater sources used for recreation in Costa Rica, as well as people’s knowledge, attitudes, and practices (KAP) profile in relation to the infection by N. fowleri.Materials and methodsWater and sediment samples were collected from 24 locations. Parameters such as temperature, pH, electrical conductivity, and dissolved oxygen in water were measured. In sediment, analyses were performed for metals, cations, and texture. Water samples were also filtered, cultured, and subjected to molecular analyses to determine the presence of FLA. Additionally, a KAP survey was conducted among 72 individuals during the fieldwork.ResultsFLA were isolated at 42 °C from 22 sites, 7 of which tested positive for Naegleria. Although some parameters were statistically associated (p < 0.05) with the presence of Naegleria, epidemiological association was not demonstrated. From the KAP survey, 37.5% of participants had never heard about N. fowleri. Average scores of 35.8% for knowledge, and 3.01 and 2.16 for attitudes and practices were obtained, with 5 being the optimum value. Significant differences (p < 0.05) between the level of knowledge by gender and geographic origin were obtained.ConclusionThis study represents a first monitoring effort to determine the frequency of FLA in surface waters of Costa Rica, indicating the presence of thermotolerant vahlkampfiid FLA in non-thermal freshwaters with the ability to proliferate at high temperatures. The KAP survey revealed a low level of knowledge and deficiencies in the management and prevention of PAM risk among the population exposed to natural freshwater reservoirs. These findings must drive health promotion, communication, and education strategies in the local population exposed to risky recreational activities.